The Serotonin Hypothesis for Depression: A Comprehensive Study (London Journal of Medical and Health Research, 2025)
It has been observed a sharp growth in the number of diagnoses of depression (under the MDD [Major Depressive Disorder] spectrum) in the last decades, accompanied by a similarly increase in sales of antidepressants in several societies, leading to depression being currently considered an epidemic (WHO). The predominant understanding of the cause for depression, the serotonin hypothesis, conveyed by 80% of the population, dates back to the 1960s, when the first antidepressants were being developed. This article sought to verify this state of affairs from the main literature available, starting from the original pharmacological development of antidepressants and their implication in the body’s physiology. Most of the literature gathered for this study did not validate the hypothesis as the most plausible main cause for depression, while nonetheless, this continues to be widespread by pharmaceutical industries and most medical practitioners as such.
Keywords: Depression; antidepressants; pharmaceutical industry; psychiatric drug research